Game-Based Learning Practices in Austrian Elementary Schools - Eliza Avdiu (ÜNİVERSİTEPARK Limited, 2019)
Contemporary literature studies show constant changes in the world of learning and teaching, and over the years game-based learning has been considered one of the most effective ways to learn something new. The purpose of this research was to understand the teaching practices used in game-based learning, and its importance in the elementary school teaching process. The study involved 24 teachers from six elementary schools in Austria. Semi-structured interviews were used. The research extended over a two-month period, including the researcher's observations and participation in classes. The results of this study are based on the descriptive analysis of teachers' views. According to the study's findings, but also from the researcher's observations, it is understood that game-based learning in Austrian elementary schools is a common teaching practice, which establishes the context of game-based learning that is fun and productive for children. Also, the results from this study illustrate the activities that teachers apply in different subjects, and show the different capacities and skills that children develop through games. According to teachers, game-based learning presents ongoing challenges related to finding and designing diverse game activities, and adapting their learning to the needs and interests of pupils.